Shedding new light on atherosclerosis therapeutics: Nanomedicines targeting atherosclerotic immune microenvironment - Zhiyue Wang; Jie Sheng; Guangming Lu; Longjiang Zhang (EngMedicine)
Atherosclerosis (AS) leads to atherosclerotic cardiovascular disease (ASCVD), the predominant cause of death worldwide. As traditional lipid-lowering therapies have encountered a bottleneck in dealing with diverse types of atherosclerotic plaques and ASCVD, alternative therapies that can target other mechanisms are urgently needed. Recent studies have revealed that AS is rooted in disrupted immune responses, such as chronic local inflammation and autoimmune responses, and immunotherapies have emerged as a nascent avenue to control plaque development owing to their satisfactory effects and high cost efficiency. The atherosclerotic immune microenvironment (AIME) is the microenvironment in which diverse immune responses occur dynamically. AIME is characterized by persistent inflammatory responses, shifted immunometabolism, and the formation of adventitial neuroimmune cardiovascular interfaces, all of which are regarded as prospective targets for AS immunotherapy. Recently, the advent of nanotechnology has advanced AS immunotherapy targeting the AIME. Manifold nanoplatforms have greatly enriched AS therapeutics owing to their multimodal imaging and multichannel intervention capabilities. Here, we offer an overview of AIME and discuss how nanomedicines can assist in AS diagnosis and intervention. We introduce nanoplatforms integrated with imaging techniques, such as magnetic resonance imaging, photoacoustic imaging, fluorescence imaging, positron emission tomography, and ultrasound imaging, which can target AIME to realize plaque diagnosis. Moreover, we elaborated on nanomaterials that regulate innate immune responses, adaptive immune responses, and aberrant immunometabolism to achieve AIME modulation. Furthermore, we highlight the possible future directions of AS therapeutics, with a focus on AIME-targeted nanomedicines.